Types of self-hurt behaviors among Chinese adolescents in Malaysia - Guan, Teik Ee; See, Ching Mey (2011)
Self-hurt among young people has raised a concern internationally. Many research suggested that self-hurt is growing significantly among young people and is becoming a public health problem in the west. Surveys revealed that adolescents and young adults are at higer risk of engaging in self-hurt behaviour. It is believed that the onset of puberty was an associated factor of self-hurt and it usually lasts five to ten years. Malaysia, as a developing country, with a population of 28.25 millions in 2010 has a relatively young population. Relatively little self-hurt research has been done in Malaysia. Although there were some counselling records found, there is virtually no study that has been designed to identify young people's self-hurt behaviour. Thus, this study aims to identify the types of self-hurt behaviour that are prevalent among the Chinese adolescents in Malaysia, the categories of severity, the association between age groups and gender in relation to types of self-hurt behaviour, and the duration of premeditation before a self-hurt act is committed.